2004
DOI: 10.1038/nature03064
|View full text |Cite
|
Sign up to set email alerts
|

Experimental demonstration of quantum memory for light

Abstract: The information carrier of today's communications, a weak pulse of light, is an intrinsically quantum object. As a consequence, complete information about the pulse cannot, even in principle, be perfectly recorded in a classical memory. In the field of quantum information this has led to a long standing challenge: how to achieve a high-fidelity transfer of an independently prepared quantum state of light onto the atomic quantum state 1-4 ? Here we propose and experimentally demonstrate a protocol for such quan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
963
1
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 818 publications
(972 citation statements)
references
References 22 publications
4
963
1
4
Order By: Relevance
“…Since the first observation of coherent retrieval of a stored optical pulse in a Bose Einstein condensate using slow light (Liu et al, 2001), interest in quantum memories has increased in the last decade (Alexander et al, 2006;Afzelius et al, 2010;Chaneliere et al, 2005. Choi et al, 2008110 Ham, 1998;Ham 2009a;Ham, 2010a;Hedges et al, 2010;Hetet et al, 2008;Hosseini et al, 2009;Julsgaard et al, 2004;Kocharovskaya et al, 2001;Kraus et al, 2006;Liu et al, 2001;Moiseev & Kroll, 2001;Moiseev et al, 2003;Neumann et al, 2009;Nilsson & Kroll, 2005;Sangouard et al, 2007;Turukhin et al, 2002;Van der Wal, et al, 2003). Because temporal multimode storage capability is required for the quantum repeaters, a photon echo-type protocol has emerged as a best candidate.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first observation of coherent retrieval of a stored optical pulse in a Bose Einstein condensate using slow light (Liu et al, 2001), interest in quantum memories has increased in the last decade (Alexander et al, 2006;Afzelius et al, 2010;Chaneliere et al, 2005. Choi et al, 2008110 Ham, 1998;Ham 2009a;Ham, 2010a;Hedges et al, 2010;Hetet et al, 2008;Hosseini et al, 2009;Julsgaard et al, 2004;Kocharovskaya et al, 2001;Kraus et al, 2006;Liu et al, 2001;Moiseev & Kroll, 2001;Moiseev et al, 2003;Neumann et al, 2009;Nilsson & Kroll, 2005;Sangouard et al, 2007;Turukhin et al, 2002;Van der Wal, et al, 2003). Because temporal multimode storage capability is required for the quantum repeaters, a photon echo-type protocol has emerged as a best candidate.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed in e.g. [5,7] the Faraday interaction ∝Ŝ zĴz causes different phase shifts on the σ + and σ − circularly polarized field components due to the population difference on the atomic magnetic sub-states, equivalent to a rotation of the linear optical polarization. Conversely, the light induced AC-Stark shift imposes a phase difference between the atomic magnetic sub-states equivalent to an optical spin rotation around the z-axis proportional to the intensity difference between σ + and σ − field components.…”
mentioning
confidence: 99%
“…In these experiments, the collective atomic population distribution on internal states is a quantum degree of freedom, and the measurement of the polarization of the light after the interaction alters the collective atomic quantum state. Measurements play an important role in the experiments reported in [5,6,7,8], but it has also been shown that multiple interactions between a light pulse and an atomic medium [9,10,11,12] suffice to effectively couple atoms and fields e.g. resulting in interspecies entanglement, atomic squeezing, or transfer of quantum states.…”
mentioning
confidence: 99%
See 2 more Smart Citations